Working Capital Management and Corporate Performance of Deposit Money Banks in Nigeria - Aduwo, Olola Olayeye; Aduwo, Ayomikun (The Journal of Accounting and Management, 2023)
This study analyzed working capital management efficiency in several banks: Access Bank, FBN Holdings, Fcmb Group, Fidelity Bank, and Guaranty Trust Bank. "CSR’s impact on corporate performance: Nigerian banks 2009-2018." Studied: Access, First, GTBank, UBA, Unity, Wema, Zenith Bank. The study analyzed how firm size affects Nigerian deposit money banks’ performance. ROA and ROE were dependent, while working capital, management, performance, and cash cycle were independent. This study employed estimation techniques including panel unit root, panel fixed effect, panel random effect, and hausman test. Stats showed platykurtic distribution in all clusters except for 2 and 3, which were lepokurtic. Working capital data is abnormal with non-zero skewness and unexpected kurtosis values. Panel regression indicates BCCC’s negative impact on ROA, while BCP, FS, and CPP have a positive impact. Optimal working capital management correlates with Nigerian deposit banks’ performance. Collect accounts receivable within credit terms for better efficiency. Sharing working capital management with stakeholders aids optimal utilization. Enhancing this will boost Nigerian banks’ profits.